PENYULUHAN MENJADI ORANG TUA HEBAT DALAM MENDIDIK ANAK (ANAK USIA DINI) DI ERA DIGITAL - Rita Nofianti (Jurnal At-Tabayyun, 2019)
The development of the digital world is not only a member of convenience, but sometimes makes clashes between children and parents, it is not uncommon to end up with a child who is defiant or other problems. Building a Family is the beginning of the birth of future generations. Family as the smallest unit in society is a place to educate and shape moral disposition and train togetherness as a provision of community life. Father-to-be and mother-to-be need to determine what kind of family is his dream, choice and hope and need to have sufficient knowledge to be a father and mother to his children. The goal of this devotion is parents, because some parents do not understand what to do when the child is abusive, emotional, contentious and so on, the bias alone parents are less active in educating the child, as the child feels he or she is not getting real attention. Thus parents should be really good at educating children, parents should be able to be some of the roles that children need, especially early childhood. Based on this, it is necessary to do activities in the form of counseling to be a great parent in educating children (early childhood) in the Digital Age.